Estimation of Phytoplankton Density in Waters Kampar River Kampar District - Dinata, Marta; Sembiring, Al Khudri; Ramadansur, Rahmat (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
The Kampar River is one of the rivers in the upper reaches that has caused pollution due to local communities such as excessive activity and gravel and sand mining. The purpose of this study was to determine the density of phytoplankton in the Kampar River in Koto Kampar Hulu Subdistrict, Kampar Regency. Purposive sampling was used to determine observation stations, which took into account habitat types and biological parameters observed such as species composition, abundance, and diversity index. The findings revealed that five classes of algae were discovered in Kampar Chlorophyceae, Cyanophyceae, Zygnematophyceae, Bacillariophyceae, and Xanthophyceae. The abundance of phytoplankton in the Kampar River's waters is classified as moderate fertility, ranging from 2,419.96 cells/liter to 3,629.96 cells/liter.